Effect of acute swimming exercise on lactate levels and its relation with zinc in pinealectomized rats - Baltaci, Abdulkerim Kasim; Cumraligil, Burhan; Kilic, Mehmet; Kaya, Oktay (Wiley, 2007)
It is argued that melatonin secreted from the pineal gland regulates the levels of zinc, which is an important trace element. Decreases in zinc levels of pinealectomized rats supports this relationship. There is an increasing amount of evidence suggesting that the pineal gland can have important effects on physical activity. The objective of the present study was to explore the changes in serum lactate levels in pinealectornized rats subjected to acute swimming exercise and its relation with zinc. Forty adult male rats of Spraque Dawley strain were equally allocated to four groups. Group 1: General Control Group. Group 2: Pinealectomized Control Group. Group 3: Swimming Control Group. Group 4: Pinealectomized Swimming Group. Serum zinc, melatonin and lactate levels were determined in the blood samples collected from the animals by a decapitation method. Zinc and melatonin levels were higher in Group I than in Groups 2, 3 and 4 (p < 0.01), higher in Group 3 than in Groups 2 and 4 (p < 0.01) and higher in Group 2 than in Group 4 (p < 0.01). The highest lactate levels were found in Group 4 (p < 0.01). Lactate levels in Group 3 were higher than those in Groups I and 2 (p < 0.01), while the levels in Groups I and 2 did not differ. Pinealectomy results in a significant increase in lactate levels in rats subjected to an acute swimming exercise. This increase in lactate levels may be associated with the decrease observed in zinc levels after pinealectomy. Copyright (C) 2006 John Wiley & Sons, Ltd.
Keywords: acute swimming exercise; pinealectomy; lactate; zinc; rat